LEGAL POLICY REGARDING REMISSION OF CRIMINALS - Luh Putu Putri Indah Pratiwi (Program Studi PPKn Universitas Pendidikan Ganesha, 2020)
This study was conducted aiming to find out how the implementation of remission rights for convicts of criminal acts of corruption in Indonesia and how the process of granting remissions against convicts of criminal acts of corruption when viewed from the perspective of Law Number. 20/2001 concerning eradicating Corruption. The research method used in writing this article is normative research that is examining by looking at the law as a norm. First, remission is still a right of convicts to a criminal act of corruption that has fulfilled the specified conditions of good behavior and has been serving a criminal sentence for more than 6 (six) months, but its implementation has been tightened to fulfill the community's sense of justice in accordance with article 34 of Government Regulation Number 99/2012 concerning Second Amendment to Government Regulation Number 32/1999 concerning the Requirements and Procedures for the Implementation of the Rights of Citizens' Guided Prisoners. Second, granting remission to corruption convicts if it is related to Law 20/2001 concerning Eradication of Corruption, the regulation of granting remission to corruption convicts must be reviewed according to the extent of losses incurred due to corruption committed by convicts to further enhance a sense of justice in Public.